Management of Paediatric Second-degree Burn in a Developing Country: With or Without Closed Dressing? (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Objective: Our objective was to observe whether second-degree burn wound management can be done without using any occlusive dressing than conventional occlusive dressing in children. The purpose of this study was to evaluate our experience and to see the results of open dressing versus closed dressing in management of second-degree burn in children.Methods: A prospective comparative study was done on children (012 years) presented with second-degree burn during the period of August 2009 to December 2010. More than 10% total burn surface area (TBSA ) involving any region of the body and any percentage of TBSA involving the hands, feet, face, and perineum were included. Patients arrived only after 24 hours after burn; burn with other systemic illnesses were excluded. By randomized controlled trial (RCT) sampling technique, study population was divided into two groupsgroup A and group B. In group A, exposure or without dressing technique was followed and in group B, occlusive dressing technique was followed.Results: 125 patients were treated in each group. Age range was from 2 months 15 days to10 years. The range of mean length of stay (LOS) in the hospital in group A was 5 to 26 days and in group B, 7 to 43 days. In group B, 42% (52) patients had wound infection, but in group A, it was only 15%. Pseudomonas infection in group B was found in 40 cases. In group A it was only in 5 patients. In group B, 94% patients needed cleaning and dressing under general anesthesia and in group A it was only 12%. Eleven patients from group B needed skin grafting, but none from group A needed it. Mean total costs of management was USD 111.13 in group A, it was USD 182.85 in group B.Conclusion: The present study demonstrated that the open or exposure or without dressing method is suitable and effective in reducing patients morbidity when compared to the closed or with occlusive dressing method for the management of second-degree burn wound in children. This method is also significantly cost effective.DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i2.37Chatt Maa Shi Hosp Med Coll J 2013; 12(2): 35-40